Transportation Infrastructure Project Financing; Highways Capital Structure Design Techniques - Hanieh Soleymani; Mehdi Ravanshadnia; Mehdi Montazer (Shock and Vibration)
Whether a private bidder can win a concession depends largely on advanced financial engineering techniques, numerous methods were developed. Meeting large infrastructure needs including its proper maintenance and operation is and will remain a major challenge for the all-around the in the coming years requiring targeted innovative financing mechanisms. Even though it is recognized that there are three types of financial instruments, equity, mezzanine finance and debt in funding an infrastructure project, the status quo is that previous capital optimization methods did not consider mezzanine finance or simply categorized it into debt-like or equity-like instruments. The global infrastructure sector is witnessing a steady growth of private equity investment in mezzanine instruments. The frequent usage of the contingent claim embedded in mezzanine financing makes the traditional model for capital structure optimization invalid. This study presents a more advanced method to optimize capital structure in infrastructure financing. This easily implemented method is based on a two-stage procedure: I) identification of optimal stopping time for convertible securities, and II) capital structure optimization by a conventional model. The quantitative optimization model can be easily generalized. The global infrastructure sector is witnessing the continued growth of a private equity fund of mezzanine tools. Repeated use of potential claims embedded in mezzanine financing has invalidated the traditional model for optimizing capital structure.